MicroRNA–21 attenuates BDE-209-induced lipid accumulation in THP-1 macrophages by downregulating Toll-like receptor 4 expression. (March 2019) - Zhi, Hui; Yuan, Na; Wu, Jiang-Ping; Lu, Lin-Ming; Chen, Xiao-Yun; Wu, Si-Kang; Mai, Bi-Xian
Abstract: Growing evidence demonstrates a possible response of specific microRNA (miRNA) to environmental pollutant stimuli in multiple biological processes. We previously reported that a persistent organic pollutant, decabromodiphenyl ether (BDE-209), can enhance Toll-like receptor 4 (TLR4)-dependent lipid uptake in THP-1 macrophages; whether miRNAs are involved in this process remains unclear. In the present study, we investigated the levels of several miRNAs related to TLR4 signaling, including miRs–9, –21, −27b, −125b, −132, −146a, −147, −155, and –let-7e, in THP-1 macrophages after stimulation by BDE-209 and oxidized low-density lipoprotein. The results showed that the levels of miR–21 were significantly suppressed by BDE-209 at concentrations of 6.25, 12.5 and 25 μM, in a dose-dependent manner; whereas there was no significant changes for the other miRNAs investigated. Moreover, the suppression of miR–21 was accompanied by an upregulated TLR4 expression, at both mRNA and protein levels. Further analysis showed that the up-regulated TLR4 induced by BDE-209 was inhibited in macrophages transfected with miR–21 mimic; meanwhile opposite results were exhibited when an anti-miR–21 inhibitor was transfected to the macrophages. Additionally, transfection with miR–21 mimic effectively attenuated BDE-209-induced lipid accumulation in macrophages. Together, these data illustrate that miR–21 inhibits BDE-209-triggered lipid accumulation in macrophages through down-regulating TLR4 expression. Highlights: BDE-209 suppressed miR-21 expression in ox-LDL-treated macrophages. Transfection with miR-21 mimic decreased TLR4 expression in the exposed macrophages. Transfection with miR-21 mimic attenuated BDE-209-induced foam cell formation. One of the few reports on the effects of POPs on miRNA expression.